Correction: Correction: A Reciprocal Model of Face Recognition and Autistic Traits: Evidence from an Individual Differences Perspective. - PLOS ONE Staff (PLoS ONE, 2015)
[This corrects the article DOI: 10.1371/journal.pone.0094013.].